(untitled) (Fiep Bulletin - online, 2011)
In the late nineteenth century, the first motion to include the discipline of Physical Education (PE) in schools was made. Since then, the association between health and movement has always been present, sometimes linked to pre-military training, or related to the distance of the population to recent political / ideological events of the time. In the 1980s changes appeared in the academic field with respect to content, methods and objectives of physical education, making it a practice not only related to the field of procedures, but also the attitudes and concepts of its conditioning. In this sense, the present study was conducted to investigate the practices developed on the subject of athletics in Basic Education schools in the city of Boa Vista, Roraima. The study included thirty (30) teachers of both sexes, aged 20 to 50 years (X=30.03±8.57 years), all volunteers. The subjects are state and municipal teachers of Basic Education, based in the metropolitan area of Boa Vista. We conducted separate interviews with closed questions and open answers. Each interview lasted an average of 20 (twenty) minutes and to support the data found, Content Analysis was used for the categorization of the results. Of the respondents, 80% mentioned the use of athletics in the content of their classes, even if just recreational or a training technique for up-coming Inter Schools Games. The most widely appreciated activities by the students were short sprinting and long jump and among the least considered are shot-put and discus throwing. Regarding the values referenced by teachers, "respect for rules and colleagues" was the most cited, which may indicate a concern, even if empirically, for the attitudes and concepts that go beyond the procedures and forms of athletics.